Xenobiotics-Division and Methods of Detection: A Review - Tea Štefanac; Dijana Grgas; Tibela Landeka Dragičević (MDPI AG, 2021)
Xenobiotics are compounds of synthetic origin, usually used for domestic, agricultural, and industrial purposes; in the environment, they are present in micropollutant concentrations and high concentrations (using ng/L to µg/L units). Xenobiotics can be categorized according to different criteria, including their nature, uses, physical state, and pathophysiological effects. Their impacts on humans and the environment are non-negligible. Prolonged exposure to even low concentrations may have toxic, mutagenic, or teratogenic effects. Wastewater treatment plants that are ineffective at minimizing the release of xenobiotic compounds are one of the main sources of xenobiotics in the environment (e.g., xenobiotic compounds reach the environment, affecting both humans and animals). In order to minimize the negative impacts, various laws and regulations have been adopted in the EU and across the globe, with an emphasis on xenobiotics removal from the environment, in a way that is economically, environmentally, and socially acceptable, and will not result in their accumulation, or creation of compounds that are more harmful. Detection methods allow detecting even small concentrations of xenobiotics in samples, but the problem is the diversity and mix of compounds present in the environment, in which it is not known what their effects are). In this review, the division of xenobiotics and their detection methods will be presented.